A prática do trabalho no desenvolvimento das competências laborais : estudo da atividade de trabalho do auxiliar operacional de fazenda experimental de Instituição de Ensino Superio - Luz, Maria de Lourdes Santiago (2015)
Driven by a social need, the managers of an experimental farm belonging to the Agricultural Science Center at an institution of higher education raised concerns about ongoing support and maintenance of the farm. During the investigation process, the difficulty of filling staff positions for agricultural operations assistants was among the managers’ concerns. The reorganization of the workforce at a public institution is subject to public tenders, protocols and resolutions established by state law, university statute and internal regulations. The qualifications or knowledge contained in the professional profile description (personal competencies for the function) for an agricultural operations assistant established by the institution allow for explicit descriptions which fail to capture the reality of the work. Therefore, the aim of this thesis was to systematize the creation of work competencies for the position of an agricultural operations assistant from the perspective of ergonomic activity in order to improve the performance of the experimental farm. For the study of work and worker competencies unique to this context, an Ergonomic Work Analysis (EWA) research protocol was used, a methodology appropriate for ergonomic activity interventions. The organization of work at the experimental farm allows for flexibility in maneuvers that favor the use and evolution of competencies depending on the sector and individual initiative. The management model that establishes discretionary power and knowledge gained by operations assistant, are unique aspects of the determinants of the labor organization studied. As an experimental farm, the research, independent of any area it advances, uses new technologies and with this, the operational competencies are understood as factors inherent in the work, in the form of actions of the operations assistant, based on the characteristic of the organization (experimental farm - agricultural unit for research and teaching).